Evaluation of Bone Repair Using a New Biphasic Synthetic Bioceramic (Plenum® Osshp) in Critical Calvaria Defect in Rats - Frigério, Paula Buzo [UNESP]; Quirino, Lilian Caldas [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; de Azambuja Carvalho, Pedro Henrique [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP] (MDPI, 2023)
(1) Background: Biphasic bioceramics are synthetic bone substitutes that provide greater safety and better predictability in guided bone regeneration. This study aimed to evaluate the bone repair process using a new biphasic bioceramic of synthetic origin (Plenum® Osshp-70HA: 30β-TCP) in critical calvarial defects. (2) Methods: seventy-four defects were created in rat calvaria and divided into two groups-Plenum® Osshp (PO), right side, and Straumann® BoneCeramic™ (BC), left side. Euthanasia was performed at 7, 15, 30, and 60 days after surgery. (3) Results: Lower gene expression was observed for runt-related transcription factor 2 (RUNX2) and vascular endothelial growth factor (VEGF) and higher expression for Integrin Binding Sialoprotein (IBSP). The results correlated with moderate immunolabeling for osteocalcin (OCN) and slight immunolabeling for osteopontin (OPN) in the PO group. Histometry showed a greater amount of biomaterial remaining in the PO group at 60 days. The microtomographic analysis showed a lower density of bone connectivity and a greater thickness of the trabeculae for the remnants of the PO group. (4) Conclusions: the Plenum® Osshp showed no differences compared to BoneCeramic™ and is therefore considered an effective option as a synthetic bone substitute in bone regeneration.